Solve the following quadratic equation. (x+12)^2=1 A. x = 11 and x = 13 B. x = -11 and x = -13 C. x = -11 and x = 13 D. x = 11 and x = -13Will make brainiest!!!

Answers

Answer 1
Answer:

Answer:

b

Step-by-step explanation:

(x+12)^2=1

or

(x+12)= +or - 1

when

x+12=1

x=1-12 =-11

when

x+12=-1

x=-1-12 =-13

then

x=-11 and x= -13

Answer 2
Answer:

Answer:

b

Step-by-step explanation:

Plato


Related Questions

What is the total interest paid on an $185,000 loan at 6.25% APR over 15 years (monthly payments)? ​
A coin is flipped three times. James is declared the winner if there are at least two tails. Peter is declared the winner if there is a head flipped.a. How many different outcomes are there?b. What is the probability that James wins?c. What is the probability that Peter wins?d. Is the game fair?e. Are there any outcomes where the game would be tied?f. Are there any outcomes where no one would win?
Which inscribed angles intercept arc RS?
Gas prices went up this week from $4.00 a gallon to $4.20. What is the percent increase of the price?
MZTRI = 3x - 5, mZIRB = x + 27,and mZTRB = 86. Find the mZTRI.

Find the perimeter and total area of the composite shape shown below. All measurements are given in inches. Use pi = 3.14 in any formulas used.

Answers

The perimeter and area of the composite shape is:

  • B. Perimeter = 19.42 inches; Area = 26.13 square inches

Recall:

Area of a circle = πr²

Perimeter of circle = 2πr

Area of triangle = 1/2(bh)

The composite shape given is composed of a triangle and a semicircle.

Perimeter of the composite shape = Perimeter of semicircle + the length of the two sides of the triangle

Perimeter = 1/2(2 × 3.14 × 3) + 2(5) = 19.42 inches

Area of the composite shape = area of semicircle + area of triangle

Area = 1/2(3.14 × 3²) + 1/2(6 × 4)

Are = 14.13 + 12

Area of the composite shape = 26.13 square inches.

Therefore, the perimeter and area of the composite shape is:

  • B. Perimeter = 19.42 inches; Area = 26.13 square inches

Learn more about area and perimeter of composite shapes on:

brainly.com/question/6317134

Answer:

Step-by-step explanation:

The composite shape consists of a semi circle and a triangle. The formula for determining the perimeter of a semicircle is expressed as

Perimeter = 1/2 × 2πr = πr

Since radius, r = 3, then

Perimeter of semi circle = 3 × 3.14 = 9.42 inches

Perimeter of composite shape = 9.42 + 5 + 5 = 19.42 inches

Area of semi circle = 1/2 × πr²

Area of semicircle = 1/2 × 3.14 × 3² = 14.13 inches²

Area of triangle = 1/2 × base × height

Area of triangle = 1/2 × 6 × 4 = 12 inches²

Area of composite shape = 14.13 + 12 = 26.13 inches²

Write the complex number 4(cos 60 + i sin 60) in standard form 10. Use DeMoivre's Theorem to find (2+3i)6

Answers

Answer:

a) The standard form of z = 4\cdot (\cos 60^(\circ)+i\cdot \sin 60^(\circ)) is z = 2 + i\cdot 2√(3), b)z = (2+i\cdot 3)^(6) = 1219.585 + i \cdot 1829.381.

Step-by-step explanation:

a) The standard form of the complex number is z = a + i\cdot b, \forall \,a,b \in \mathbb{R}. If we get that z = 4\cdot (\cos 60^(\circ)+i\cdot \sin 60^(\circ)), whose standard form is obtained by algebraic means:

1)z = 4\cdot (\cos 60^(\circ)+i\cdot \sin 60^(\circ)) Given

2)z = (4\cdot \cos 60^(\circ))+i\cdot (4\cdot \sin 60^(\circ)) Distributive and Associative properties.

3)z = 2 + i\cdot 2√(3) Multiplication/Result.

The standard form of z = 4\cdot (\cos 60^(\circ)+i\cdot \sin 60^(\circ)) is z = 2 + i\cdot 2√(3).

b) The De Moivre's Theorem states that:

z = (a+i\cdot b)^(n)= r^(n)\cdot (\cos \theta + i\cdot \sin \theta)

Where:

r =\sqrt{a^(2)+b^(2)} and \theta = \tan^(-1) \left((b)/(a)\right).

If we know that z = (2+i\cdot 3)^(6), then:

r = \sqrt{2^(2)+3^(2)}

r =√(13)

r \approx 3.606

\theta = \tan^(-1)\left((3)/(2) \right)

\theta \approx 56.310^(\circ)

The resulting expression is:

z = 3.606^(6)\cdot (\cos 56.310^(\circ)+i\cdot \sin 56.310^(\circ))

z = 1219.585+i\cdot 1829.381

Therefore, z = (2+i\cdot 3)^(6) = 1219.585 + i \cdot 1829.381.

What volume is shown in the graduated cylinder below?Lector inmersivo(1 Punto)
20.4ml
28 ml
30 ml
24

Answers

Answer:

resposta letra 28ml njm

A typical person has an average heart rate of 70.0 70.0 beats/min. Calculate the given questions. How many beats does she have in 6.0 6.0 years? How many beats in 6.00 6.00 years? And finally, how many beats in 6.000 6.000 years? Pay close attention to significant figures in this question.

Answers

Answer:

a) 2.2 × 10⁸ beats

b) 2.20 × 10⁸ beats

c) 2.207 × 10⁸ beats

Step-by-step explanation:

Data provided in the question:

Average heart rate of a typical person = 70.0 beats/min

Now,

In the given cases, the significance is on the significant figures after the decimal

Therefore,

the answer is will be provided accordingly

Now,

a) Time = 6.0 years

[since 1 significant figure after decimal. answer will be give in  1 significant figure after decimal ]

time in minutes = 6.0 × 365 × 24 × 60

= 3.1 × 10⁶ minutes

Total beats = Average heart rate × Time

= 70 × 3.1 × 10⁶

= 2.2 × 10⁸ beats

b)  Time = 6.00 years

[since 2 significant figure after decimal. answer will be give in 2 significant figure after decimal ]

time in minutes = 6.00 × 365 × 24 × 60

= 3.15 × 10⁶ minutes

Total beats = Average heart rate × Time

= 70 × 3.15 × 10⁶

= 2.20 × 10⁸ beats

c) Time = 6.000 years

[since 3 significant figure after decimal. answer will be give in 3 significant figure after decimal ]

time in minutes = 6.000 × 365 × 24 × 60

= 3.154 × 10⁶ minutes

Total beats = Average heart rate × Time

= 70 × 3.154 × 10⁶

= 2.207 × 10⁸ beats

suppose a ladder 20 feet long is placed against a vertical wall 20 feet high. How far would the top of the ladder move down the wall by pulling out the bottom of the ladder by 5 feet?

Answers

the ladder would now be 15 feet long

 Find 5 consecutive whole numbers if it is known that the sum of the squares of the first 3 numbers is equal to the sum of the squares of the last 2 numbers.

Answers

so... our numbers... let's say the first one is hmmm "a"
so the second and subsequent are
a
a+1
a+2
a+3
a+4

there, 5 consecutive whole numbers or integers for that matter

now, we know the sum of the square of the first three,
is the same as the sum of the square of the last two

so \bf \begin{cases}a\na+1\na+2\n\textendash\textendash\textendash\textendash\na+3\na+4\end{cases}\qquad (a)^2+(a+1)^2+(a+2)^2=(a+3)^2+(a+4)^2

do a binomial theorem expansion on those, solve for "a"